2022
DOI: 10.1038/s41467-022-33755-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological invasions as a selective filter driving behavioral divergence

Abstract: Biological invasions are a multi-stage process (i.e., transport, introduction, establishment, spread), with each stage potentially acting as a selective filter on traits associated with invasion success. Behavior (e.g., exploration, activity, boldness) plays a key role in facilitating species introductions, but whether invasion acts as a selective filter on such traits is not well known. Here we capitalize on the well-characterized introduction of an invasive lizard (Lampropholis delicata) across three indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…We argue that the reason for this outcome lies in the individual-level behavioural plasticity of the non-indigenous population, making behavioural choices in similar tests nonrepeatable. These findings fit with the higher behavioural plasticity reported in recent studies on non-indigenous species (Chapple et al, 2022;Damas-Moreira et al, 2019). Increased behavioural plasticity is thought to support organisms to cope with novel environmental, allowing them to rapidly adjust their behaviour to the new environmental conditions, particularly during the early stages of invasion, where invaders are characterized by small population sizes that are susceptible to environmental and demographic stochasticity (Chapple et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We argue that the reason for this outcome lies in the individual-level behavioural plasticity of the non-indigenous population, making behavioural choices in similar tests nonrepeatable. These findings fit with the higher behavioural plasticity reported in recent studies on non-indigenous species (Chapple et al, 2022;Damas-Moreira et al, 2019). Increased behavioural plasticity is thought to support organisms to cope with novel environmental, allowing them to rapidly adjust their behaviour to the new environmental conditions, particularly during the early stages of invasion, where invaders are characterized by small population sizes that are susceptible to environmental and demographic stochasticity (Chapple et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…The Phenotypic Plasticity Hypothesis (Torchyk & Jeschke, 2018) suggests that alien species should display a higher degree of plasticity than natives (Richards et al, 2006), enabling the expression of more advantageous phenotypes, like the ability to access to novel resources in new environments (Grey & Jackson, 2012;Reisinger et al, 2017;Sol et al, 2002Sol et al, , 2005Sol et al, , 2011Sol & Lefebvre, 2000), the expression of anti-predator behaviour (Hazlett et al, 2003;Reisinger et al, 2017) and flexible habitat choice (Grey & Jackson, 2012;Stroud et al, 2019). However, only recently research has started focusing on the role of behavioural traits and their plasticity in promoting invasion success at the individual and population levels (e.g., Damas-Moreira et al 2019, Brand et al, 2021Chapple et al, 2022;Cordeschi et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For instance in the American signal crayfish (Pacifastacus leniusculus), Daniels and Kemp (2022) found repeatable differences in shy-bold type behaviour that predicted individual motivation to disperse by passing through weirs (though not successful at doing so). Invasion processes could, therefore, be considered a 'selective filter' whereby only individuals with appropriate combinations of personality and other traits can invade a novel environment successfully (Chapple et al, 2022). Working on the same species of crayfish, Pintor et al (2008), found that invasive populations were bolder and more aggressive on average than populations within their native range.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used 57 adult male delicate skinks (Lampropholis delicata) to evaluate the stability of consistent among-individual differences in behaviour, as well as syndrome structures, across short (four weeks) and long (five months) timeframes. Consistent amongindividual variation in behavioural traits as well as their correlation has already been extensively studied in this species, where individuals were found to exhibit a well-characterized activity-exploration syndrome (Michelangeli et al 2016a(Michelangeli et al ,b, 2018(Michelangeli et al , 2019(Michelangeli et al , 2020Moule et al 2016;Goulet et al 2017a,b;Chung et al 2017), which has been linked to its success as an invasive species (Chapple et al 2011(Chapple et al , 2012(Chapple et al , 2022Chapple and Wong 2016;Hamilton et al 2020) and urban adapter (Moule et al 2016;Kang et al 2018;Walsh et al 2018). Despite the extent of this research, measurements were limited to two datapoints per individual taken over short time frames [three days to two weeks (Michelangeli et al 2016a(Michelangeli et al , b, 2018(Michelangeli et al , 2019(Michelangeli et al , 2020Moule et al 2016;Goulet et al 2017a,b;Chung et al 2017)].…”
Section: Introductionmentioning
confidence: 90%